EVALUASI VALUE PROPOSITION PADA USAHA KECIL PARANI CAR WASH - Anarta Pratama, Rinanda Bagus; Liliani, Liliani (Universitas Nahdlatul Ulama Surabaya, 2017)
This study aimed to evaluate the Value Proposition in Parani Car Wash, a home-call car cleaning startup business. The Value Proposition is viewed as part of Osterwalder’s Business Model Canvas and the SWOT approach is used to describe and explain the current Value Proposition of Parani Car Wash. This research uses qualitative approach with descriptive analysis. Data collection method in this study is using semi-structured interview technique. There are 9 informants interviewed, consisting of two customers of the company, two of the owners of similar companies, an expert, and four managers of the company. The results of SWOT approach indicates the strength of the Value Proposition is aligned with the needs of customers, while the weakness is related to network. Opportunities are available regarding expansion of operational areas and service variants, but there are threats related to competition.